GENETIC DIVERSITY AND FRUIT QUALITY OF SEVERAL POMELO “JERUK BALI” (Citrus grandis L. Osbeck) CULTIVARS IN BALI - Ida Bagus Komang Mahardika; I Nyoman Rai; Made Sudiana Mahendra; Rindang Dwiyani (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2017)
This study aimed to determine the genetic diversity and fruits quality of the